Transindividual Equations/Matrices - Zander Porter (Performance Philosophy, 2023)
This writing (thinking-feeling) unfolds (an articulation of) contemporary (dis)embodiment through specified glances at the "(post-)internet,” schizoid relationality, and network/device/identity matrices. Technogenetic (and hormonal) play and transductions for transindividuality on the transparency-obfuscation (or personality/anonymity) binaries arrive as psychotherapeutics for symphonic moving-sensing-feeling-thinking-communicating in a potentiated post-neoliberal matrix (networking). Generated is a set of direction-possibilities for a post-internet-bodied world consumed by a hegemony of individualizations and self-captures, desiring instead towards queerer ceremonies and telepathic forms of (care-)presence/therapy for being-together-alone (individuation). The concurrent/included choreographic and research-artistic work 3M0T1NGn3tw0rk1ng peeks into a technogenetic xeno-spacetime containing relating (meta-)selves.